Spotlight on Zebrafish: Translational Impact - Patton, E. Elizabeth (The Company of Biologists Limited, 2014)
In recent years, the zebrafish has emerged as an increasingly prominent model in biomedical research. To showcase the translational impact of the model across multiple disease areas, Disease Models & Mechanisms has compiled a Special Issue that includes thought-provoking reviews, original research reporting new and important insights into disease mechanisms, and novel resources that expand the zebrafish toolkit. This Editorial provides a summary of the issue’s contents, highlighting the diversity of zebrafish disease models and their clinical applications.